Efficient Differentiation of Bone Marrow Mesenchymal Stem Cells into Endothelial Cells in Vitro. (February 2018) - Wang, Chengen; Li, Yuan; Yang, Min; Zou, Yinghua; Liu, Huihui; Liang, Zeyin; Yin, Yue; Niu, Guochen; Yan, Ziguang; Zhang, Bihui
Abstract : Objective: Endothelial cells (ECs) play an important role in neovascularisation, but are too limited in number for adequate therapeutic applications. Mesenchymal stem cells (MSCs) have the potential to differentiate into endothelial lineage cells, which makes them attractive candidates for therapeutic angiogenesis. The aim of this study was to investigate efficient differentiation of MSCs into ECs by inducing medium in vitro . Methods: MSCs were isolated from bone marrow by density gradient centrifugation. The characterisation of the MSCs was determined by their cluster of differentiation (CD) marker profile. Inducing medium containing vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), insulin like growth factor (IGF), epidermal growth factor (EGF), ascorbic acid, and heparin was applied to differentiate the MSCs into ECs. Endothelial differentiation was quantitatively evaluated using flow cytometry. Real time quantitative PCR (qRT-PCR) was used to analyse mRNA expression of endothelial markers. Tube formation assay was further performed to examine the functional status of the differentiated MSCs. Results: Flow cytometry analysis demonstrated that CD31 + and CD34 + cells increased steadily from 12% at 3 days, to 40% at 7 days, and to 60% at 14 days. Immunofluorescence staining further confirmed the expression of CD31 and CD34. qRT-PCR showed that expression of von Willebrand factor (vWF), vascular endothelial cadherin (VE-cadherin) and vascular endothelial growth factor receptor-2 (VEGFR-2) were significantly higher in the induced MSCs group compared with the uninduced MSCs group. The functional behavior of the differentiated cells was tested by tube formation assay in vitro on matrigel. Induced MSCs were capable of developing capillary networks, and progressive formation of vessel like structures was associated with increased EC population. Conclusions: These results provide a method to efficiently promote differentiation of MSCs into ECs in vitro for potential application in the treatment of peripheral arterial disease.